Clinical pharmacological studies with prazosin during pregnancy complicated by hypertension. - Rubin, P C (1983)
The disposition and effect of orally administered prazosin have been studied in eight women with hypertension which was uncontrolled by beta-adrenoceptor blockade during the last trimester of pregnancy. Results were compared with healthy men of similar age. The median time to peak concentration was 165 min during pregnancy and 120 min in the men (P less than 0.04). Area under the concentration vs time curve was 3914 ng l-1 min in pregnancy and 2439 ng l-1 min in the men (P less than 0.06). Mean elimination half-life was 171 min in the pregnant women and 130 min in the men (P less than 0.01). Blood pressure was lowered by prazosin in both supine and standing positions. Blood pressure control remained satisfactory in six of the eight women and the median prolongation of pregnancy was 22 days. Neonatal outcome was satisfactory and all babies are developing normally. We conclude that prazosin is more slowly, but apparently more completely, absorbed during pregnancy and that its half-life is slightly prolonged. Prazosin appears to be both effective and safe when used during the last trimester to control blood pressure.